Poorer but less poor notes on the Philippine poverty trends 2000-2003 - Edillon, Rosemarie G.; Piza, Sharon Faye A. (The Philippine Review of Economics, 2005)
This paper attempts to shed light on the debate sparked by the seemingly conflicting trend from 2000 to 2003 where we note a decrease in real incomes accompanied by a decrease in poverty incidence. A comparison of income and expenditure figures across space and over time gives us two important lessons: The first is that in order to have a radical impact on poverty reduction, we really need to bring the economy to a higher growth path. The second is that lapses in economic performance, even if only momentary, are costly in terms of poverty reduction efforts. We recommend that a comprehensive poverty alleviation program should include a macro growth strategy, efforts to improve linkages between the high-growth and broad-based sectors of the economy, and measures to address vulnerabilities among those who will graduate out of poverty.